PENGARUH PENYESUAIAN DIRI TERHADAP STRES AKADEMIK PADA MAHASISWA FAKULTAS PSIKOLOGI UNJANI DALAM PEMBELAJARAN JARAK JAUH : - - Mediasari, Dita; Ayu Nyoman Ratu Ningrum, Iga; Amanda Metra, Litra (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Adjusting to the new learning environment during the COVID-19 pandemic has been a substantial challenge for student, especially on their levels of academic stress, a concern that remains relevant even in the post-pandemic era. This research investigates the influence of self-adjustment on academic stress among students participating in distance learning at the Faculty of Psychology, Universitas Jenderal Achmad Yani. Employing a non-experimental quantitative approach with a causal design, the study involved 80 students selected through accidental sampling who completed online questionnaires, including a self-adjustment scale based on Hurlock's theory (?=0,873, item validity 0,3 – 0,54) and the Perceived Stress Scale (PSS-10) developed by Cohen (?=0,741, item validity 0,35 - 0,82). Data were analyzed using simple linear regression after testing for normality and linearity assumptions. The results revealed a significant negative effect of self-adjustment on academic stress, with a significance value of p = 0.000 and a coefficient of determination R² = 0.269. This indicates that higher levels of self-adjustment are associated with lower levels of academic stress. The regression equation obtained was Y = 162.573 - 0.809X. Additional findings showed that senior students tend to have better self-adjustment. The study concludes that self-adjustment acts as a protective factor against academic stress in distance learning settings. These findings underscore the importance of strengthening psychological adaptation programs and student coping strategies in the digital and hybrid learning era. This research contributes to the development of higher education policies and psychological support services tailored to student needs. ABSTRAK Transformasi pembelajaran akibat pandemi COVID-19 telah membawa tantangan signifikan terhadap penyesuaian diri dan tingkat stres akademik mahasiswa, yang tetap relevan meski pandemi telah usai. Penelitian ini bermaksud mengetahui bagaimana peran penyesuaian diri terhadap stres akademik mahasiswa dalam konteks pembelajaran jarak jauh di Fakultas Psikologi UNJANI. Penelitian ini merupakan penelitian kuantitatif non-eksperimental dengan rancangan kausal. Sampel terdiri dari 80 mahasiswa yang dipilih menggunakan teknik accidental sampling dan mengisi kuesioner daring yang terdiri dari skala penyesuaian diri berdasarkan teori Hurlock dengan hasil uji alat ukur ?=0,873, validitas item rentang 0.3 – 0,54 serta Perceived Stress Scale (PSS-10) dari Cohen dengan nilai ? = 0,741, validitas item 0,35-0,82. Data dianalisis menggunakan uji regresi linear sederhana setelah melalui pengujian asumsi normalitas dan linearitas. Hasil analisis menunjukkan adanya pengaruh negatif yang signifikan dari penyesuaian diri terhadap stres akademik, nilai signifikansi p = 0,000 dan koefisien determinasi R² = 0,269. Semakin tinggi penyesuaian diri, semakin rendah tingkat stres akademik mahasiswa. Persamaan regresi yang diperoleh adalah Y = 162,573 - 0,809X. Temuan tambahan menunjukkan bahwa mahasiswa angkatan lebih tua memiliki penyesuaian diri yang lebih baik. Simpulan utama dari penelitian ini adalah penyesuaian diri berperan sebagai faktor protektif terhadap stres akademik mahasiswa dalam pembelajaran daring. Implikasi dari hasil ini menekankan pentingnya penguatan program adaptasi psikologis dan strategi coping mahasiswa di era pembelajaran digital dan hybrid. Penelitian ini memberikan kontribusi penting bagi institusi pendidikan tinggi dalam merancang kebijakan akademik dan layanan pendampingan psikologis berbasis kebutuhan mahasiswa.